Epigenetic responses to Phytophthora citrophthora gummosis in citrus. (December 2021) - Rodrigues da Silva, Adielle; da Costa Silva, Delmira; dos Santos Pinto, Kaliane Nascimento; Santos Filho, Hermes Peixoto; Coelho Filho, Maurício Antônio; dos Santos Soares Filho, Walter; Ferreira, Cláudia Fortes; da Silva Gesteira, Abelmon
Highlights: DNA methylation is a defense mechanism in citrus. Plant immunity responds to methylated DNA. Full and hemimethylated DNA levels confer resistance of citrus to P . citrophthora . Citrus rootstock-scion combinations pass-on DNA methylation imprints. The present study confirms (epi)genetic inheritance of resistance to biotic stress in citrus. Abstract: Studies show that DNA methylation is associated with plant immunity but little is known as to how this epigenetic mechanism assists plants in adjusting their responses to biotic stress, especially when interacting with an hemibiotrophic pathogen such as citrus Phytophthora . The aim of the present study was to assess the effects of scion-rootstock interaction on plant resistance to P. citrophthora infection and DNA methylation patterns in 'Pera' sweet orange and 'Tahiti' acid lime grafted onto 'Rangpur' lime and 'Tropical' sunki rootstocks reinoculated with P. citrophthora . Results showed that reinoculated plants of the 'Pera' sweet orange/'Rangpur' lime and 'Tahiti' acid lime/'Tropical' sunki combinations with more and less sensitive varieties to Phytophthora, presented smaller stem lesions and increased frequency of full methylation and hemimethylation rates, compared to inoculated plants. In contrast, 'Tahiti' acid lime/'Rangpur' lime, two highly sensitive varieties, and 'Pera'/'Tropical' sunki, two much less sensitive varieties, showed high increases in the frequency of hemimethylation and non-methylation levels. Results suggest that in citrus, both the scion-rootstock interaction and DNA methylation affect the response to P. citrophthora infection. Reinoculated plants, depending on the combination, showed changes in intracellular hyphae growth through the formation of sets of fibers and crystal accumulation in the periderm, cortex, and phloem. In addition, starch grain concentration was higher in reinoculated plants in comparison to inoculated plants. These findings support the assumption that DNA methylation is a plant defense mechanism and therefore may be exploited to improve the response of plants to the gummosis of P. citrophthora in citrus.